Description of the Psychological Dynamics of Male Victims of Sexual Abuse (Case Study of Pedophilia among Children in Makassar City) - Muhammad Faiz Muttaqi Sukri; Sitti Murdiana (Polteknik Ilmu Pemasyarakatan, 2023)
Pedophilia is a sexual disorder that involves sexual attraction towards children. Pedophilia is committed by adults against children. This study aims to find out how the psychological dynamics of male victims of pedophilia are described and what are the impacts of pedophile victims. The respondents of this study were adult men (victims of pedophilia). This study uses qualitative methods with semi-structured interview techniques. Research data techniques using driven data analysis. The results of the data show that the victim would not be aware of expressing it directly. This was motivated by the victim's age and knowledge of sexuality. Sexual abuse will affect the victim's life in the next development. The impact felt by the victim is that the respondent experiences psychological sexual pathological disorders such as post-incident trauma, and deviations in appetite. Other psychological changes felt by respondents such as withdrawing from the environment, changes in sexual orientation, to negative feelings and thoughts about oneself. The negative impact of understanding on children can be suppressed through support from the social environment and also partners. The results of this study are expected to contribute in the form of references, information, data, about the psychological dynamics of male victims of pedophilia.